2017
DOI: 10.21162/pakjas/17.5102
|View full text |Cite
|
Sign up to set email alerts
|

APPLICATION OF Dalbergia sissoo BIOCHAR ENHANCED WHEAT GROWTH, YIELD AND NUTRIENT RECOVERY UNDER REDUCED FERTILIZER DOSES IN CALCAREOUS SOIL

Abstract: In a field trial, Dalbergia sissoo biochar was used to investigate its potential for improving growth, yield and nutrient recovery of wheat (Triticum aestivum L.), at varying fertilizer rates under calcareous soil. Two biochar levels (0.0 and 1.0% of soil weight) were used along with five fertilizer rates i.e. 0, 25, 50, 75 and 100% of recommended inorganic fertilizer dose (RFD). Seeds of wheat cultivar Faisalabad-2008 were sown in the field using 2 factorial-randomized complete block design. At reduced fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
4
0
2
Order By: Relevance
“…EB-2+UEB-2 developed from the combination of growth promoting organics like seaweed and humic acid. Hamdani et al (2017) also reported that wheat grown under application of recommended fertilizer dose along with biochar resulted in maximum increase in plant height (33%).…”
Section: Resultsmentioning
confidence: 93%
“…EB-2+UEB-2 developed from the combination of growth promoting organics like seaweed and humic acid. Hamdani et al (2017) also reported that wheat grown under application of recommended fertilizer dose along with biochar resulted in maximum increase in plant height (33%).…”
Section: Resultsmentioning
confidence: 93%
“…Por ello, podría sugerirse que la mayor altura registrada, en el presente estudio, pudo deberse a tal efecto, puesto que se realizó la aplicación de potasio junto con el BC. Asimismo, Fawad et al (2017) registraron hasta 33% mayor AP cuando aplicaron BC en relación al control; ellos concluyeron que el BC disminuye la pérdida de los fertilizantes aplicados, debido a su capacidad de adsorción. En este mismo sentido Ahmad et al (2011) y Torres-Moya et al (2016 mencionan que con la adición de fertilizantes se mejora el desarrollo del cultivo de avena.…”
Section: Resultados Y Discusiónunclassified
“…Por otro lado, el BC ha influido positivamente sobre las poblaciones y la actividad de los microorganismos benéf icos para las especies vegetales (Akhtar et al, 2015;Liao et al, 2016;Tripti et al, 2017). Por consiguiente, impactos positivos sobre la germinación (Clay et al, 2016), crecimiento y desarrollo de los cultivos (Pérez- Salas et al, 2013;Fawad et al, 2017;Liu et al, 2017a), y producción de biomasa pueden ser generados (Lou et al, 2016). Esto podría traducirse en mejores rendimientos de los cultivos (Mackie et al, 2015;Dai et al, 2016;Plaza et al, 2016;Zhang et al, 2016b;Mia et al, 2017;Trupiano et al, 2017).…”
Section: Introductionunclassified
“…According to Ref. [ 47 ]; 1% biochar combined with lower fertilizer doses can successfully boost wheat growth, yield, nutritional content, and absorption. When compared to merely fertilizer application, the synergistic effect of charcoal plus fertilizer treatments enhances yield [ 48 ].…”
Section: Discussionmentioning
confidence: 99%